Cognitive Behavior Therapy (CBT) Experimentation in Reducing Students' Academic Anxiety - Bachtiar, Andy; Suharmawan, Wahid; Mawaddati, Ika Romika (Konseling Edukasi : Journal of Guidance and Counseling, 2026)
Cognitive Behavior Therapy (CBT) Experimentation in Reducing Students' Academic Anxiety. This study aims to test the effectiveness of individual counseling with a Cognitive Behavioral Therapy (CBT) approach in reducing academic anxiety in eleventh-grade students at SMK Muhammadiyah Jember. Using a true experimental design with a pretest-posttest control group design, this study involved 60 students (N=60) selected through purposive sampling technique based on the criteria of high academic anxiety scores. Subjects were randomly divided into an experimental group (n=30) who received six sessions of CBT intervention, and a control group (n=30) who were on the waitlist (waitlist control group). The intervention process focused on identifying cognitive distortions related to vocational demands, restructuring negative thoughts, and self-regulation training. Data were analyzed using an independent sample t-test. The results of the statistical test showed a very strong significant difference between the two groups (t = -23.86, p < .001), where the experimental group at SMK Muhammadiyah Jember showed a drastic decrease in academic anxiety compared to the control group. These findings prove that CBT techniques are effective in increasing motivation and concentration in learning through modifying technical mindsets. Practically, these results can be adopted by guidance and counseling teachers in vocational high schools as an evidence-based clinical protocol (evidence-based practice) to address students' psychological barriers in facing the burden of assignments and practical exams.Keywords: Cognitive Behavioral Therapy, Individual Counseling, Learning Problems, Experiments.